2009
DOI: 10.2460/javma.234.9.1162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three treatment regimens for sheep and goats with caseous lymphadenitis

Abstract: Acceptable alternatives to opening, draining, and flushing of lesions may exist for treatment of sheep and goats with caseous lymphadenitis. Use of tulathromycin and penicillin in this study constituted extralabel drug use, which would require extended withholding times before milk or meat of treated sheep and goats can be sold for human consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 3 publications
1
27
0
Order By: Relevance
“…The high sensitivity to other antibiotics is justifiable, since the breeders of the study area do not make regular use of antibiotics in goat and sheep raising (Abreu et al 2008). Nevertheless, antimicrobial sensitivity in vivo is less, because this bacterium induces the formation of a fibrous capsule, which prevents contact between the drug used and the pathogen (Baird & Fontaine 2007, Washburn et al 2009). A study held at UK and Bursa/Turkey, tested three protocols of antimicrobial therapy for caseous lymphadenitis in sheep and goats, using penicillin G and tulathromycin, but they were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high sensitivity to other antibiotics is justifiable, since the breeders of the study area do not make regular use of antibiotics in goat and sheep raising (Abreu et al 2008). Nevertheless, antimicrobial sensitivity in vivo is less, because this bacterium induces the formation of a fibrous capsule, which prevents contact between the drug used and the pathogen (Baird & Fontaine 2007, Washburn et al 2009). A study held at UK and Bursa/Turkey, tested three protocols of antimicrobial therapy for caseous lymphadenitis in sheep and goats, using penicillin G and tulathromycin, but they were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antimicrobials to treat abscesses is recommended by some authors, though with controversial results (Abreu et al 2008, Washburn et al 2009). These two options are important because they aim to reduce the spread of the pathogen in the environment, which occurs at the time of rupture of the abscess (Baird & Fontaine 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In other study, Washburn et al [3] compared three antibiotics for treatment of CLA abscesses: surgical drainage and flushing followed by subcutaneous procaine penicillin G;…”
Section: Discussionmentioning
confidence: 98%
“…The longlasting properties of this formulation of the drug and its high degree of lipid solubility may allow it to enter encapsulated abscesses and achieve adequate intracellular concentrations. In our laboratory, we demonstrated that systemic tulathromycin was as effective as traditional lancing and flushing in resolving CL lesions in sheep and goats (7), suggesting that tulathromycin could penetrate into abscesses to therapeutic concentrations.…”
mentioning
confidence: 94%
“…In sheep and goats, attempts at treatment and control of CL have included lancing of peripheral abscesses and flushing the newly opened abscess with potentiated iodine solutions, systemic antimicrobial treatment, surgical removal of abscesses, intralesional injection of formalin, isolation of affected animals from other animals to prevent disease spread, and culling affected animals (3,7). Although antibacterial protocols have been used for pharmacologic treatment of animals with CL (7), clinical resolution of lesions has not been consistently achieved.…”
mentioning
confidence: 99%